Development of Semi Automatic H-Ometer Equipment - Salsidu, Mohd Sal (2002)
Semi Automatic H-Ometer (SAHO) equipment was developed to enhance H-Ometer testing. The SAHO was developed using a total design concept, which involved proposed design and specifications, conceptual design, detailed design, and fabrication and testing. The conceptual design was the most critical stage in the design process and two methods were used in the design of SAHO. The methods were the Product Design Specification (PDS) and Morphological Chart (MC). Based on these methods, eight possible concepts were generated. The Pugh selection method was used for the final selection of possible concepts and a combination of concepts 5 and 7 was chosen. Based on selected concepts, SAHO consists of seven major parts which are casing, vertical mover, sliding unit, stand, control unit, Automatic Probe Changer (APC) and sample stand. The major parts were modeled using AutoCAD software while the analysis of the critical parts were undertaken with Finite Element Analysis (FEA). The SAHO is likely to enhance H-Ometer testing as it will have the capability to test a variety of sample materials.